Obesity in the Early Childhood Years: State of the Science and Implementation of Promising Solutions: Workshop in Brief - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine
On October 6, 2015, the Roundtable on Obesity Solutions of the National Academies of Sciences, Engineering, and Medicine held a workshop titled \

Obesity in the Early Childhood Years: State of the Science and Implementation of Promising Solutions: Workshop Summary - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Among the many troubling aspects of the rising prevalence of obesity in the United States and elsewhere in recent years, the growth of early childhood overweight and obesity stands out. To explore what is known about effective and innovative interventions to counter obesity in young children, the National Academies of Sciences, Engineering, and Medicine2019s Roundtable on Obesity Solutions held a workshop in October 2015. The workshop brought together many of the leading researchers on obesity in young children to describe the state of the science and potential solutions based on that research. Participants explored sustainable collaborations and new insights into the implementation of interventions and policies, particularly those related to nutrition and physical activity, for the treatment and prevention of obesity in young children. Obesity in the Early Childhood Years summarizes the presentations and discussions from the workshop.

Examining a Developmental Approach to Childhood Obesity: The Fetal and Early Childhood Years: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
Recent scientific evidence points to the origins of childhood obesity as an outcome of the dynamic interplay of genetic, behavioral, and environmental factors throughout early development, with a compelling body of evidence suggesting that both maternal and paternal nutritional and other exposures affect a child's risk of later obesity. The burgeoning field of epigenetics has led researchers to speculate that many of the observed associations between early developmental exposures and later risk of childhood obesity are mediated, at least in part, through epigenetic mechanisms. To explore the body of evolving science that examines the nexus of biology, environment, and developmental stage on risk of childhood obesity, the Institute of Medicine and the National Research Council convened a workshop in February 2015. The workshop focused on the prenatal period, infancy, and early childhood and addressed evidence from both animal and human studies. Workshop objectives were to (1) identify epigenetic-mediated relationships between exposure to risk factors during sensitive periods of development (gestation through age 3) and subsequent obesity-related outcomes; (2) explore the science around periods of plasticity and potential reversibility of obesity risk in the context of early childhood development; and (3) examine the translation of epigenetic science to guide early childhood obesity prevention and intervention to reduce obesity risk. This report summarizes the information presented and discussed at the workshop.

Physical Activity: Moving Toward Obesity Solutions: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
In 2008, the U.S. federal government issued fully approved physical activity guidelines for the first time. The idea that physical activity impacts health can be traced as far back as Hippocrates, and the science around the linkages between physical activity and health has continuously accumulated. On April 14-15, 2015, the Institute of Medicine2019s Roundtable on Obesity Solutions held a 2-day workshop to explore the state of the science regarding the impact of physical activity in the prevention and treatment of overweight and obesity and to highlight innovative strategies for promoting physical activity across different segments of the population. This report summarizes the presentations and discussions from this workshop.

Physical Activity: Moving Toward Obesity Solutions: Workshop in Brief - Institute of Medicine
On April 14-15, 2015, the Roundtable on Obesity Solutions held a 2-day workshop titled \

Measuring Progress in Obesity Prevention: Workshop Report - Institute of Medicine (The National Academies Press, 2012)
Nearly 69 percent of U.S. adults and 32 percent of children are either overweight or obese, creating an annual medical cost burden that may reach 147 billion. Researchers and policy makers are eager to identify improved measures of environmental and policy factors that contribute to obesity prevention. The IOM formed the Committee on Accelerating Progress in Obesity Prevention to review the IOM's past obesity-related recommendations, identify a set of recommendations for future action, and recommend indicators of progress in implementing these actions. The committee held a workshop in March 2011 about how to improve measurement of progress in obesity prevention.

Bridging the Evidence Gap in Obesity Prevention: A Framework to Inform Decision Making - Institute of Medicine (The National Academies Press, 2010)
To battle the obesity epidemic in America, health care professionals and policymakers need relevant, useful data on the effectiveness of obesity prevention policies and programs. Bridging the Evidence Gap in Obesity Prevention identifies a new approach to decision making and research on obesity prevention to use a systems perspective to gain a broader understanding of the context of obesity and the many factors that influence it.

The Current State of Obesity Solutions in the United States: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
For the first time in decades, promising news has emerged regarding efforts to curb the obesity crisis in the United States. Obesity rates have fallen among low-income children in 18 states, the prevalence of obesity has plateaued among girls, regardless of ethnicity, and targeted efforts in states such as Massachusetts have demonstrably reduced the prevalence of obesity among children. Although the reasons for this turnaround are as complex and multifaceted as the reasons for the dramatic rise in obesity rates in recent decades, interventions to improve nutrition and increase physical activity are almost certainly major contributors. Yet major problems remain. Diseases associated with obesity continue to incur substantial costs and cause widespread human suffering. Moreover, substantial disparities in obesity rates exist among population groups, and in some cases these disparities are widening. Some groups and regions are continuing to experience increases in obesity rates, and the prevalence of severe obesity is continuing to rise. The Current State of Obesity Solutions in the United States is the summary of a workshop convened in January 2014 by the Institute of Medicine Roundtable on Obesity Solutions to foster an ongoing dialogue on critical and emerging implementation, policy, and research issues to accelerate progress in obesity prevention and care. Representatives of public health, health care, government, the food industry, education, philanthropy, the nonprofit sector, and academia met to discuss interventions designed to prevent and treat obesity. The workshop focused on early care and education, schools, worksites, health care institutions, communities and states, the federal government, and business and industry. For each of these groups, this report provides an overview of current efforts to improve nutrition, increase physical activity, and reduce disparities among populations.

Alliances for Obesity Prevention: Finding Common Ground: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
Many organizations are making focused efforts to prevent obesity. To achieve their goals, accelerate their progress, and sustain their success, the assistance of many other individuals and groups–not all of them with a singular focus on obesity prevention–will be essential. In October 2011 the Institute of Medicine held a workshop that provided an opportunity for obesity prevention groups to hear from and hold discussions with many of these potential allies in obesity prevention. They explored common ground for joint activities and mutual successes and lessons learned from efforts at aligning diverse groups with goals in common.

Community Perspectives on Obesity Prevention in Children: Workshop Summaries - Institute of Medicine (The National Academies Press, 2009)
As the public health threat of childhood obesity has become clear, the issue has become the focus of local, state, and national initiatives. Many of these efforts are centered on the community environment in recognition of the role of environmental factors in individual behaviors related to food and physical activity. In many communities, for example, fresh produce is not available or affordable, streets and parks are not amenable to exercise, and policies and economic choices make fast food cheaper and more convenient than healthier alternatives. Community efforts to combat obesity vary in scope and scale; overall, however, they remain fragmented, and little is known about their effectiveness. At the local level, communities are struggling to determine which obesity prevention programs to initiate and how to evaluate their impact. In this context, the Institute of Medicine held two workshops to inform current work on obesity prevention in children through input from individuals who are actively engaged in community- and policy-based obesity prevention programs. Community perspectives were elicited on the challenges involved in undertaking policy and programmatic interventions aimed at preventing childhood obesity, and on approaches to program implementation and evaluation that have shown promise. Highlights of the workshop presentations and discussions are presented in this volume.

Cross-Sector Responses to Obesity: Models for Change: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
Obesity affects 17 percent of children and adolescents and almost 36 percent of adults in the United States. Conservative estimates suggest that obesity now accounts for almost 20 percent of national health care spending. Until the obesity epidemic is reversed, obesity will continue to drive rates of chronic diseases such as heart disease, stroke, type 2 diabetes, and certain types of cancer. Cross-Sector Responses to Obesity is a summary of a workshop convened by the Institute of Medicine Roundtable on Obesity Solutions in September 2014 to explore models of cross-sector work that may reduce the prevalence and consequences of obesity. This report identifies case studies of cross-sector initiatives that engage partners from diverse fields, and lessons learned from and barriers to established cross-sector initiatives.

Driving Action and Progress on Obesity Prevention and Treatment: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine
The Roundtable on Obesity Solutions of the Health and Medicine Division of the National Academies of Sciences, Engineering, and Medicine held a workshop in Washington, DC, on September 27, 2016, titled \

Driving Action and Progress on Obesity Prevention and Treatment: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
After decades of increases in the obesity rate among U.S. adults and children, the rate recently has dropped among some populations, particularly young children. What are the factors responsible for these changes? How can promising trends be accelerated? What else needs to be known to end the epidemic of obesity in the United States? To examine these and other pressing questions, the Roundtable on Obesity Solutions, of the National Academies of Sciences, Engineering, and Medicine, held a workshop in September 2016. The workshop brought together leaders from business, early care and education, government, health care, and philanthropy to discuss the most promising approaches for the future of obesity prevention and treatment. This publication summarizes the presentations and discussions from the workshop.

Accelerating Progress in Obesity Prevention: Solving the Weight of the Nation - Institute of Medicine (The National Academies Press, 2012)
One-third of adults are now obese, and children's obesity rates have climbed from 5 to 17 percent in the past 30 years. The causes of the nation's obesity epidemic are multi-factorial, having much more to do with the absence of sidewalks and the limited availability of healthy and affordable foods than a lack of personal responsibility. The broad societal changes that are needed to prevent obesity will inevitably affect activity and eating environments and settings for all ages. Many aspects of the obesity problem have been identified and discussed; however, there has not been complete agreement on what needs to be done to accelerate progress. Accelerating Progress in Obesity Prevention reviews previous studies and their recommendations and presents five key recommendations to accelerate meaningful change on a societal level during the next decade. The report suggests recommendations and strategies that, independently, can accelerate progress, but urges a systems approach of many strategies working in concert to maximize progress in accelerating obesity prevention. The recommendations in Accelerating Progress in Obesity Prevention include major reforms in access to and opportunities for physical activity; widespread reductions in the availability of unhealthy foods and beverages and increases in access to healthier options at affordable, competitive prices; an overhaul of the messages that surround Americans through marketing and education with respect to physical activity and food consumption; expansion of the obesity prevention support structure provided by health care providers, insurers, and employers; and schools as a major national focal point for obesity prevention. The report calls on all individuals, organizations, agencies, and sectors that do or can influence physical activity and nutrition environments to assess and begin to act on their potential roles as leaders in obesity prevention.

Educating the Student Body: Taking Physical Activity and Physical Education to School - Institute of Medicine (The National Academies Press, 2013)
Physical inactivity is a key determinant of health across the lifespan. A lack of activity increases the risk of heart disease, colon and breast cancer, diabetes mellitus, hypertension, osteoporosis, anxiety and depression and others diseases. Emerging literature has suggested that in terms of mortality, the global population health burden of physical inactivity approaches that of cigarette smoking. The prevalence and substantial disease risk associated with physical inactivity has been described as a pandemic. The prevalence, health impact, and evidence of changeability all have resulted in calls for action to increase physical activity across the lifespan. In response to the need to find ways to make physical activity a health priority for youth, the Institute of Medicine's Committee on Physical Activity and Physical Education in the School Environment was formed. Its purpose was to review the current status of physical activity and physical education in the school environment, including before, during, and after school, and examine the influences of physical activity and physical education on the short and long term physical, cognitive and brain, and psychosocial health and development of children and adolescents. Educating the Student Body makes recommendations about approaches for strengthening and improving programs and policies for physical activity and physical education in the school environment. This report lays out a set of guiding principles to guide its work on these tasks. These included: recognizing the benefits of instilling life-long physical activity habits in children; the value of using systems thinking in improving physical activity and physical education in the school environment; the recognition of current disparities in opportunities and the need to achieve equity in physical activity and physical education; the importance of considering all types of school environments; the need to take into consideration the diversity of students as recommendations are developed. This report will be of interest to local and national policymakers, school officials, teachers, and the education community, researchers, professional organizations, and parents interested in physical activity, physical education, and health for school-aged children and adolescents.

The Current State of Obesity Solutions in the United States: Workshop in Brief - Institute of Medicine
On January 7, 2014, the newly formed Roundtable on Obesity Solutions of the Institute of Medicine held its first public event, a half-day workshop titled \

Evaluating Obesity Prevention Efforts: A Plan for Measuring Progress - Institute of Medicine (The National Academies Press, 2013)
Obesity poses one of the greatest public health challenges of the 21st century, creating serious health, economic, and social consequences for individuals and society. Despite acceleration in efforts to characterize, comprehend, and act on this problem, including implementation of preventive interventions, further understanding is needed on the progress and effectiveness of these interventions. Evaluating Obesity Prevention Efforts develops a concise and actionable plan for measuring the nation's progress in obesity prevention efforts2014specifically, the success of policy and environmental strategies recommended in the 2012 IOM report Accelerating Progress in Obesity Prevention: Solving the Weight of the Nation. This book offers a framework that will provide guidance for systematic and routine planning, implementation, and evaluation of the advancement of obesity prevention efforts. This framework is for specific use with the goals and strategies from the 2012 report and can be used to assess the progress made in every community and throughout the country, with the ultimate goal of reducing the obesity epidemic. It offers potentially valuable guidance in improving the quality and effect of the actions being implemented. The recommendations of Evaluating Obesity Prevention Efforts focus on efforts to increase the likelihood that actions taken to prevent obesity will be evaluated, that their progress in accelerating the prevention of obesity will be monitored, and that the most promising practices will be widely disseminated.

Early Childhood Obesity Prevention Policies - Institute of Medicine (The National Academies Press, 2011)
Childhood obesity is a serious health problem that has adverse and long-lasting consequences for individuals, families, and communities. The magnitude of the problem has increased dramatically during the last three decades and, despite some indications of a plateau in this growth, the numbers remain stubbornly high. Efforts to prevent childhood obesity to date have focused largely on school-aged children, with relatively little attention to children under age 5. However, there is a growing awareness that efforts to prevent childhood obesity must begin before children ever enter the school system. Early Childhood Obesity Prevention Policies reviews factors related to overweight and obese children from birth to age 5, with a focus on nutrition, physical activity, and sedentary behavior, and recommends policies that can alter children's environments to promote the maintenance of healthy weight. Because the first years of life are important to health and well-being throughout the life span, preventing obesity in infants and young children can contribute to reversing the epidemic of obesity in children and adults. The book recommends that health care providers make parents aware of their child's excess weight early. It also suggests that parents and child care providers keep children active throughout the day, provide them with healthy diets, limit screen time, and ensure children get adequate sleep. In addition to providing comprehensive solutions to tackle the problem of obesity in infants and young children, Early Childhood Obesity Prevention Policies identifies potential actions that could be taken to implement those recommendations. The recommendations can inform the decisions of state and local child care regulators, child care providers, health care providers, directors of federal and local child care and nutrition programs, and government officials at all levels.

Progress in Preventing Childhood Obesity: How Do We Measure Up? - Institute of Medicine (The National Academies Press, 2007)
The remarkable increase in the prevalence of obesity among children and youth in the United States over a relatively short timespan represents one of the defining public health challenges of the 21st century. The country is beginning to recognize childhood obesity as a major public health epidemic that will incur substantial costs to the nation. However, the current level of investment by the public and private sectors still does not match the extent of the problem. There is a substantial underinvestment of resources to adequately address the scope of this obesity crisis. At this early phase in addressing the epidemic, actions have begun on a number of levels to improve the dietary patterns and to increase the physical activity levels of young people. Schools, corporations, youth-related organizations, families, communities, foundations, and government agencies are working to implement a variety of policy changes, new programs, and other interventions. These efforts, however, generally remain fragmented and small in scale. Moreover, the lack of systematic monitoring and evaluation of interventions have hindered the development of an evidence base to identify, apply, and disseminate lessons learned and to support promising efforts to prevent childhood obesity. Progress in Preventing Childhood Obesity: How Do We Measure Up? examines the progress made by obesity prevention initiatives in the United States from 2004 to 2006. This book emphasizes a call to action for key stakeholders and sectors to commit to and demonstrate leadership in childhood obesity prevention, evaluates all policies and programs, monitors their progress, and encourages stakeholders to widely disseminate promising practices. This book will be of interest to federal, state, and local government agencies; educators and schools; public health and health care professionals; private-sector companies and industry trade groups; media; parents; and those involved in implementing community-based programs and consumer advocacy.

Legal Strategies in Childhood Obesity Prevention: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Since 1980, childhood obesity rates have more than tripled in the United States. Recent data show that almost one-third of children over 2 years of age are already overweight or obese. While the prevalence of childhood obesity appears to have plateaued in recent years, the magnitude of the problem remains unsustainably high and represents an enormous public health concern. All options for addressing the childhood obesity epidemic must therefore be explored. In the United States, legal approaches have successfully reduced other threats to public health, such as the lack of passive restraints in automobiles and the use of tobacco. The question then arises of whether laws, regulations, and litigation can likewise be used to change practices and policies that contribute to obesity. On October 21, 2010, the Institute of Medicine (IOM) held a workshop to bring together stakeholders to discuss the current and future legal strategies aimed at combating childhood obesity. Legal Strategies in Childhood Obesity Prevention summarizes the proceedings of that workshop. The report examines the challenges involved in implementing public health initiatives by using legal strategies to elicit change. It also discusses circumstances in which legal strategies are needed and effective. This workshop was created only to explore the boundaries of potential legal approaches to address childhood obesity, and therefore, does not contain recommendations for the use of such approaches.